GYROTROPIC PROPERTIES OF SHALLOWEST SAND-CLAY SEDIMENTS, AS DETERMINED FROM ACOUSTIC MEASUREMENTS IN BOREHOLES - Obolentseva I.R.; Nefedkin Yu.A.; Krylov D.V. (My University, 2000)
Gyrotropic properties of clayey sands and sandy clays have been investigated by acoustic measurements at frequencies of about 400 Hz in up to 18 m deep boreholes, using a special contact sonde with piezoelectric transducers. The source transducers were placed on opposite borehole walls and acted alternately in radial opposite directions; the receiver piezoelements, also radially oriented, were positioned 1.4 m away from the plane, circlewise at each 60°. The polarization processing of the obtained oscillation spectra allowed us to estimate both the azimuthal frequency characteristics of the symmetrical wave-field part and the parameters of the ellipses reflecting wave-field dissymmetry. The gyration and attenuation constants were determined from ellipse rotation angles (relative to source direction) and ellipticity, under the assumption of a gyrotropic medium. The behavior of ellipse parameters has been investigated as a function of oscillation frequency and S-wave velocity. A comparison of the obtained parameters with those determined earlier for similar sand-clay sediments showed that gyration constants at frequencies of about 400 Hz are some what smaller than those at seismic frequencies (10 to 100 Hz), but ellipse rotation angles are greater, being directly proportional to frequency.